GANGGUAN BERBAHASA PSIKOGENIK PADA REMAJA BERBICARA MANJA - Darpito, Danu (Journal of Education for The Language and Literature of Indonesia, 2024)
Abstract: Indeed, children must go through a phase where children acquire a language and the process of developing the child's own language as it grows. Basically, children's ability to acquire and develop a language has different levels. Some are directly without a hitch and some have a language disorder. One of them is psychogenic language disorder. However, researchers will examine and analyze psychogenic language disorders on the behavior of a teenager in spoiled speech. The purpose of this study is (1) to describe the forms of a phonological disorder produced by adolescents who behave in spoiled speech, (2) to analyze the factors of a teenager who behaves by speaking spoiled. This research uses descriptive qualitative methods and case studies. The subject of the study was a 15 year old female teenager. The results showed that the phonological errors experienced by teenager X on phoneme replacement contained 13 phonological error data, 3 phonological error data on adding phonemes, and there were 4 phonological error data on phoneme omission in every speech of speakers who had language disorders in spoiled speaking style. And it is indicated that there are environmental factors in the family and in the past when giving attention or affection to teenager X which resulted in being spoiled until adolescence.